Porto do Capim: mobilização e resistência nas redes sociais - Silva, Irley David Fabricio da (2018)
This paper aims to study the articulation strategies of Porto do Capim community on Facebook and Youtube. By using the hashtag #PortodoCapim on Instagram, we explored the perspective of others to understand how they see this community, traditionally known as a riverside one. It is necessary to know if others confirm (or collide with) the public authorities’ speech about the place: derelict, uncultured, damaged, etc. We used documentary, bibliographic, interpretive, natnographic and exploratory researches. Moreover, we collected network environment specific data from Porto do Capim’s Facebook, Youtube and Instagram profiles. What we found reveals a community that spare no efforts to fight the interests of those who want them to leave the space where they have lived for over 70 years. Social media give visibility to their cause, traditions and memories as a place of speaking and resistance. The tools of these media (events, videos, texts, images, groups, etc.) were marshalled to make their claims organized, legitimate and accepted by the people from Joao Pessoa.